LEGAL POLICY ANALYSIS: PLASTIC BAG WASTE REDUCTION STRATEGY WITH NOKEN BAGS IN JAYAWIJAYA REGENCY - Irna, Irna; YM, Hardiyanti; Asso, Fajar Sidik (EKSEKUSI, 2025)
Jayawijaya Regency, a region rich in natural resources, faces significant challenges in plastic waste management. The use of Noken bags as an environmentally friendly alternative to plastic bags is a strategic step that requires analysis from a legal policy perspective. The purpose of this paper is to analyze legal policies related to reducing plastic bag waste, assess the effectiveness of Noken bags as an alternative to plastic bags, and analyze the challenges and obstacles in implementing plastic waste reduction policies. This paper utilizes a qualitative research method, focusing on legal policy analysis, combined with a survey method to obtain public perceptions of Noken bags as an alternative to plastic bags. The study concludes that the plastic waste problem in Jayawijaya is urgent due to the ever-increasing volume and minimal management infrastructure, resulting in serious impacts on the environment and health. Although Noken bags have the potential to be an environmentally friendly alternative, limited production and price are obstacles. Therefore, a comprehensive strategy is needed, encompassing waste management facilities, an effective 3R program, education, economic support, and strong regulations to make Noken a sustainable solution.